Budaya Mutu dalam Peningkatan Kinerja Pendidikan: Sebuah Kajian Sistematis atas Strategi Kepemimpinan dan Penjaminan Mutu di Lembaga Pendidikan (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Improving the quality of education has become a strategic issue in efforts to strengthen the competitiveness and credibility of educational institutions in the era of globalization. One crucial approach to achieving this goal is developing a quality culture as a system of values, attitudes, and habits oriented towards continuous improvement. This article aims to systematically review how the concept of quality culture is applied in the educational context and answer the question: how do strategies for strengthening quality culture contribute to improving the performance of educational institutions? This research uses a qualitative approach using the Literature Review (LR) method. The data sources were scientific articles from 2020–2025 accessed through Google Scholar and Publish or Perish (PoP) with the keyword "quality culture." Of the 30 articles found, 5 were selected for thematic analysis. The review results revealed three main trends: (1) the importance of academic leadership and supervision in fostering a quality culture, (2) the role of internal quality assurance systems in consistent quality implementation, and (3) the impact of quality culture on improving institutional performance. In conclusion, quality culture is a key element in the success of sustainable education. Further research is recommended to examine digital-based and collaborative quality culture models.